let i, j be Nat; :: thesis: for G being Go-board st 1 <= i & i <= len G & 1 <= j & j + 2 <= width G holds
(LSeg ((G * (i,j)),(G * (i,(j + 1))))) /\ (LSeg ((G * (i,(j + 1))),(G * (i,(j + 2))))) = {(G * (i,(j + 1)))}

let G be Go-board; :: thesis: ( 1 <= i & i <= len G & 1 <= j & j + 2 <= width G implies (LSeg ((G * (i,j)),(G * (i,(j + 1))))) /\ (LSeg ((G * (i,(j + 1))),(G * (i,(j + 2))))) = {(G * (i,(j + 1)))} )
assume that
A1: ( 1 <= i & i <= len G ) and
A2: 1 <= j and
A3: j + 2 <= width G ; :: thesis: (LSeg ((G * (i,j)),(G * (i,(j + 1))))) /\ (LSeg ((G * (i,(j + 1))),(G * (i,(j + 2))))) = {(G * (i,(j + 1)))}
now :: thesis: for x being object holds
( ( x in (LSeg ((G * (i,j)),(G * (i,(j + 1))))) /\ (LSeg ((G * (i,(j + 1))),(G * (i,(j + 2))))) implies x = G * (i,(j + 1)) ) & ( x = G * (i,(j + 1)) implies x in (LSeg ((G * (i,j)),(G * (i,(j + 1))))) /\ (LSeg ((G * (i,(j + 1))),(G * (i,(j + 2))))) ) )
let x be object ; :: thesis: ( ( x in (LSeg ((G * (i,j)),(G * (i,(j + 1))))) /\ (LSeg ((G * (i,(j + 1))),(G * (i,(j + 2))))) implies x = G * (i,(j + 1)) ) & ( x = G * (i,(j + 1)) implies x in (LSeg ((G * (i,j)),(G * (i,(j + 1))))) /\ (LSeg ((G * (i,(j + 1))),(G * (i,(j + 2))))) ) )
hereby :: thesis: ( x = G * (i,(j + 1)) implies x in (LSeg ((G * (i,j)),(G * (i,(j + 1))))) /\ (LSeg ((G * (i,(j + 1))),(G * (i,(j + 2))))) )
assume A4: x in (LSeg ((G * (i,j)),(G * (i,(j + 1))))) /\ (LSeg ((G * (i,(j + 1))),(G * (i,(j + 2))))) ; :: thesis: x = G * (i,(j + 1))
then reconsider p = x as Point of () ;
A5: x in LSeg ((G * (i,j)),(G * (i,(j + 1)))) by ;
A6: p in LSeg ((G * (i,(j + 1))),(G * (i,(j + 2)))) by ;
j <= j + 2 by NAT_1:11;
then A7: j <= width G by ;
A8: j + 1 < j + 2 by XREAL_1:6;
then A9: j + 1 <= width G by ;
A10: 1 <= j + 1 by NAT_1:11;
then (G * (i,(j + 1))) `1 = (G * (i,1)) `1 by
.= (G * (i,j)) `1 by ;
then A11: p `1 = (G * (i,(j + 1))) `1 by ;
j < j + 1 by XREAL_1:29;
then (G * (i,j)) `2 < (G * (i,(j + 1))) `2 by ;
then A12: p `2 <= (G * (i,(j + 1))) `2 by ;
(G * (i,(j + 1))) `2 < (G * (i,(j + 2))) `2 by ;
then p `2 >= (G * (i,(j + 1))) `2 by ;
then p `2 = (G * (i,(j + 1))) `2 by ;
hence x = G * (i,(j + 1)) by ; :: thesis: verum
end;
assume x = G * (i,(j + 1)) ; :: thesis: x in (LSeg ((G * (i,j)),(G * (i,(j + 1))))) /\ (LSeg ((G * (i,(j + 1))),(G * (i,(j + 2)))))
then ( x in LSeg ((G * (i,j)),(G * (i,(j + 1)))) & x in LSeg ((G * (i,(j + 1))),(G * (i,(j + 2)))) ) by RLTOPSP1:68;
hence x in (LSeg ((G * (i,j)),(G * (i,(j + 1))))) /\ (LSeg ((G * (i,(j + 1))),(G * (i,(j + 2))))) by XBOOLE_0:def 4; :: thesis: verum
end;
hence (LSeg ((G * (i,j)),(G * (i,(j + 1))))) /\ (LSeg ((G * (i,(j + 1))),(G * (i,(j + 2))))) = {(G * (i,(j + 1)))} by TARSKI:def 1; :: thesis: verum